The Influence Of Leadership Style And Work Motivation On The Performance Of Employees Of The Kaur District Satpol Pp Office - Muslimin, Herlian; E. G, Ida Ayu Made; Fitriano, Yun; Yulianti , Oni; Harwini , Dewi (Universitas Dehasen Bengkulu, 2025)
The purpose of this study was to determine and analyze the influence between leadership style and work motivation variables on employee performance at the Kaur Regency Satpol PP Office. The sampling technique used was a saturated sample technique where the entire population of Kaur Regency Satpol PP Office employees as many as 118 people were used as samples. Data collection techniques used questionnaires and interviews. This study used qualitative descriptive techniques with data analysis techniques using multiple linear analysis and classical assumption tests. Data processing used SPSS software version 20. The results obtained found no significant influence on leadership style on employee performance based on the results of t count smaller than t table (1.322 <2.018) and significance greater than the specified significance (0.193> 0.05). Different results showed a significant influence of work motivation variables on employee performance based on the results of t count greater than t table (2.620> 2.018) and significance greater than the specified significance (0.012 <0.05). Overall, the variables of leadership style and work motivation have a simultaneous effect on employee performance with a determination coefficient of 9.5%.